A three-dimensional simulation and process analysis of tropospheric ozone depletion events (ODEs) during the springtime in the Arctic using CMAQ (Community Multiscale Air Quality Modeling System) - L. Cao; S. Li; Y. Gu; Y. Luo (Atmospheric Chemistry and Physics, 2023)
The tropospheric ozone depletion event (ODE), first observed at Barrow (now known as Utqiaġvik), Alaska, is a phenomenon that frequently occurs during the springtime in the Arctic. In this study, we performed a three-dimensional model study on ODEs occurring at Barrow and its surrounding areas between 28 March and 6 April 2019 using a 3-D multi-scale air quality model, CMAQ (Community Multiscale Air Quality Modeling System). Several ODEs observed at Barrow were captured, and two of them were thoroughly analyzed using the process analysis method to estimate contributions of horizontal transport, vertical transport, dry deposition, and the overall chemical process to the variations in ozone and bromine species during ODEs. We found that the ODE occurring between 30 and 31 March 2019 (referred to as ODE1) was primarily caused by the horizontal transport of low-ozone air from the Beaufort Sea to Barrow. The formation of this low-ozone air over the sea was largely attributed to a release of sea-salt aerosols from the Bering Strait under strong wind conditions, stemming from a cyclone generated on the Chukotka Peninsula. It was also discovered that the surface ozone dropped to less than 5 ppb over the Beaufort Sea, and the overall chemical process contributed up to 10 ppb to the ozone loss. Moreover, BrO over the sea reached a maximum of approximately 80 ppt. This low-ozone air over the sea was then horizontally transported to Barrow, leading to the occurrence of ODE1. Regarding another ODE on 2 April (ODE2), we found that its occurrence was also dominated by the horizontal transport from the sea, but under the control of an anticyclone. The termination of this ODE was mainly attributed to the replenishment of ozone-rich air from the free troposphere by a strong vertical transport.